1997
DOI: 10.1016/s0022-5223(97)70321-0
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic correction of the syndrome of prolapsing right coronary aortic cusp, dilatation of the sinus of valsalva, and ventricular septal defect

Abstract: Anatomic correction of all the components of the syndrome of prolapsing right coronary cusp, dilatation of the sinus of Valsalva, and ventricular septal defect, can be achieved by a very simple technique. This technique can be applied in young children and prevents progression and secondary changes. Early correction in all patients with this syndrome is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
54
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(59 citation statements)
references
References 14 publications
2
54
0
3
Order By: Relevance
“…Such patients raise the concern that progressive deformity of the right coronary cusp will lead to significant AR. 13,14 In the patients of the present series, the deformity did not progress, and in only 1 of the 5 was it complicated by AR that did not progress for 9 years after the onset. We detected trivial AR in another patient who had a tiny jet across the outlet septum; however, there was no associated abnormality of the right coronary cusp.…”
Section: Discussionmentioning
confidence: 52%
“…Such patients raise the concern that progressive deformity of the right coronary cusp will lead to significant AR. 13,14 In the patients of the present series, the deformity did not progress, and in only 1 of the 5 was it complicated by AR that did not progress for 9 years after the onset. We detected trivial AR in another patient who had a tiny jet across the outlet septum; however, there was no associated abnormality of the right coronary cusp.…”
Section: Discussionmentioning
confidence: 52%
“…However, once the aortic lesion becomes evident, sophisticated valve reconstruction techniques need to be taken into consideration [Bonhoeffer et al, 1992;Yacoub et al, 1997].…”
Section: Ventricular Septal Defectmentioning
confidence: 99%
“…Yacoub et al [17] reported that a lack of continuity between the aortic media, annulus of aortic valve and the ventricular septum is the basic structural abnormality in patients with any type of VSD complicated by aortic valve prolapse and regurgitation. However, it does not entirely explain why most large perimembranous defects, that are closely related to the aortic valve and deficient in its septal support, are less frequently associated with aortic valve prolapse with or without regurgitation, than are subarterial VSDs with similar anatomy.…”
Section: Discussionmentioning
confidence: 99%